2008
DOI: 10.1103/physrevlett.100.112502
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Single-Particle and Collective Effects in the Odd-ACu Isotopes beyondN=40

Abstract: Collective properties of the low-lying levels in the odd-A 67-73Cu were investigated by Coulomb excitation with radioactive beams. The beams were produced at ISOLDE and postaccelerated by REX-ISOLDE up to 2.99 MeV/u. In 67,69Cu, low-lying 1/2(-), 5/2(-), and 7/2(-) states were populated. In 71,73Cu, besides the known transitions deexciting the single-particle-like 5/2(-) and core-coupled 7/2(-) levels, gamma rays of 454 and 135 keV, respectively, were observed for the first time. Based on a reanalysis of beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 25 publications
5
59
0
Order By: Relevance
“…The analysis of the Coulomb excitation data on 69,71,73 Cu was published previously in [22]. This work shows the population of 1/2 − , 5/2 − , and 7/2 − levels.…”
Section: Discussionmentioning
confidence: 67%
“…The analysis of the Coulomb excitation data on 69,71,73 Cu was published previously in [22]. This work shows the population of 1/2 − , 5/2 − , and 7/2 − levels.…”
Section: Discussionmentioning
confidence: 67%
“…Earlier β-decay, Coulomb excitation, and multinucleon transfer reaction studies showed rather complicated level sequences in the neutron-rich 69-73 Cu isotopes, caused by different excitation modes [13][14][15][16][17][18]. The low-lying 5=2 − and 7=2…”
mentioning
confidence: 95%
“…The data revealed the presence of both single-particle and collective states at low energy in the neutronrich Cu nuclei that drop with increasing value of N and lie at approximately the same energy. This behavior illustrates the sensitivity of the transition rates to the details of the wave functions [18]. 70 Zn.…”
Section: Isomeric Beams Of Cu Isotopesmentioning
confidence: 82%
“…Simultaneously experiments along the chains of neutron-rich Ni, Cu and Zn isotopes were pursued in order to study collective and single particle properties in the vicinity of N=40 and the doubly-magic configuration at 78 Ni [16][17][18][19][20][21][22][23][24][25][26][27][28]. Moreover, the first g-factor measurement of excited states was successfully performed with a radioactive ion beam at ISOLDE in this region [24].…”
mentioning
confidence: 99%